ChemInform Abstract: Chemo‐ and Stereoselective Synthesis of Fluorinated Enamides from Ynamides in HF/Pyridine: Second‐Generation Approach to Potent Ureas Bioisosteres. Issue 32 (August 2015) - Metayer, Benoit; Compain, Guillaume; Jouvin, Kevin; Martin‐Mingot, Agnes; Bachmann, Christian; Marrot, Jerome; Evano, Gwilherm; Thibaudeau, Sebastien
Abstract The corresponding mixtures of E and Z isomers can be easily separated by flash chromatography.